Towards the supply chain integration for consumer electronics industry - Ng, Tsong Jye. (2008)
The objective of the project is to enhance the planning and forecasting operations through the supply chain initiative. The project is also proposes the supply chain management solution with the proposed system design. The implementation of the SCM solution will be based on the CPRF project model.